1987
DOI: 10.1016/s0006-3495(87)83249-6
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channels in Southern Bean Mosaic Virus Capsid

Abstract: The study of southern bean mosaic virus protein coat high resolution model revealed a structure with properties of a natural protein-ion channel. Coat protein pentamers form a 30-A long channel and the amino acid composition of its wall bears some homology with the pentameric structure proposed for the nicotinic acetylcholine receptor channel. Ion transport properties were analyzed by computing ion-protein interaction energies on the basis of quantum chemistry methods. Energy maps show a channel attractive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 16 publications
5
10
0
Order By: Relevance
“…During the equilibration phase and also during force-probe simulations, no water permeated the capsid. This observation is in accordance with the results of Silva et al (54), who reported a high energy barrier of E ¼ 300 kcal/mol for water at the gate along the fivefold symmetry axis. No other position on the protein shell exhibited a gate for possible water or ion permeation, which is in good agreement with the lack of water flux in our simulations.…”
Section: Water Permeation Friction and Surface Effectssupporting
confidence: 93%
“…During the equilibration phase and also during force-probe simulations, no water permeated the capsid. This observation is in accordance with the results of Silva et al (54), who reported a high energy barrier of E ¼ 300 kcal/mol for water at the gate along the fivefold symmetry axis. No other position on the protein shell exhibited a gate for possible water or ion permeation, which is in good agreement with the lack of water flux in our simulations.…”
Section: Water Permeation Friction and Surface Effectssupporting
confidence: 93%
“…The magnitudes of the energies calculated using the simple Langevin-dipole representation of water are much more reasonable than the many hundreds of kcal/M calculated in an earlier model of the 4SBV channelog [82] which did not include water. However, the profile is not satisfactory quantitatively, for it implies impossibly slow ion exchange for a ring of carbonyl oxygens.…”
Section: Free Energy Profile For a Viral Channelog Whose Selectivity supporting
confidence: 48%
“…1 based upon the crystallographic data for 4SBV [82,83]. The left and right views are both from the external perspective but differ in that they show the positions of the H atoms in the selectivity filter when these have been rotated maximally away from the channel axis (left) and maximally towards it (right).…”
Section: A Speculative Structure J?)r the Acetylcholine Receptor Channelmentioning
confidence: 99%
“…The specific domains that form these channels remain to be defined. A pore structure has been proposed to exist at the center of pentameric subunits (at fivefold axes) in the protein shell of icosahedral viruses (20). However, we do not think that this pore structure forms the channels described here.…”
Section: Discussionmentioning
confidence: 74%